Negotiations in a Business context: what has happened since 2007?: review article (2005-2020) - Sulayman, Shirin Jamal (المجلة العلمية للدراسات و البحوث المالية و التجارية : علمية محكمة., 2023)
The purpose of this review paper is to provide insights in business negotiation research today. this study attempts to identify the most recent research topics and trends. this review is based on the earlier work by Henrik Agndal (2007) which carried out a business negotiation literature review for the period from 1996 to 2005. for the purpose of this project an additional 70 peer reviewed articles covering the period from 2005 to 2020 were reviewed. the literature review exercise has resulted in a confirmation of the Henrik Agndal (2007) model. the dominant research topics continue to exist. however there is a shift of interest represented by the size the academic production justified by business environment needs. leading to an important research production in: technology and negotiation; culture and negotiation and individual variables and negotiation. results and recommendations reflects on the important and trending business negotiation research topics. الغرض الأساسي من تلك المقالة الخاصة بمراجعة الأدبيات هو تقديم رؤى في أبحاث مفاوضات الأعمال اليوم، حيث تقوم هذه الدراسة بالتعرف على أحدث الموضوعات والاتجاهات البحثية مستندة في ذلك على مشروع العمل السابق الذي قام به Henrik Andal (۲۰۰۷) والذي أجرى مراجعة أدبيات مفاوضات الأعمال التجارية خلال الفترة من ١٩٩٦ إلى 2005. وبعد مراجعة ما يقرب من ۷۰ مقال تغطي الفترة من ٢٠٠٥ إلى ۲۰۲۰ وبالتركيز بشكل أساسي على الأبحاث والدراسات التي تم إجراؤها بالأعوام ۲۰۱۸، ۲۰۱۹ و۲۰۲۰ توصلت الدراسة إلى التأكيد على محتوي نموذج Henrik Agndal (۲۰۰۷) من كون مواضيع البحث المهيمنة لا تزال قائمة. ومع ذلك، فإن هناك تحول في الاهتمام يتمثل في زيادة حجم الإنتاج الأكاديمي الناتج عن احتياجات بيئة العمل. مما أدى إلى إنتاج بحثي مهم في مجال: التكنولوجيا والتفاوض وكذا الثقافة والتفاوض، والمتغيرات الفردية والتفاوض. وقد أكدت نتائج وتوصيات الدراسة على أهمية الانتباه لأبحاث مفاوضات الأعمال.